Developing a Javanese Language Module Through The Savi (Somatic, Auditory, Visual, Intellectual) Approach to Improve Learning Outcomes And Speaking Skills of Fourth-Grade Students at MI Perwanida, Blitar City - Febrian Dwi Kartika Sari (JOSAR (Journal of Students Academic Research), 2026)
This study aims to develop a Javanese language learning module based on the SAVI (Somatic, Auditory, Visual, Intellectual) approach to improve learning outcomes and speaking skills of fourth grade students at MI Perwanida Blitar city. The research employs a Research Development (R&D) design adapted from Borg and Gall's ten step model including research, product design,testing, validation, and dissemination. Data were collected through observation, interviews, questionaires, and pre-tet-post test assesments, analyzed both quantitative and qualitative methods. The result show that the  develop modul meets the criteria of validity, practicality, and effectivness. Validation from material and media experts rated the module as" very valid",indicating it's feasibility fro classroom implementation. Statistical analysis revealed significant improvement in students' learning outcomes and speaking abilities, particularly  in vocabulary mastery and apropriate use of 'unggah-ungguh' (speech levels) Both teachers and students responded positiveley to the module's design, content, and activities. The SAVI  based module effectively creates an engaging, interactive and culturaly meaningful learning environment, helping students internalize Javanese Moral and cultural values. Thus, this module can serve as an innovative and character-oriented learning medium for Javanese Language instruction in elementary schools